Confirming the Mediation Effect of A Structural Model By Using Bootstrap Approach: A Case Study of Malaysian 8th Grade Students’ Mathematics Achievement - Aimran, Ahmad Nazim; Ahmad, Sabri; Afthanorhan, Asyraf (International Journal of Business, Economics and Management, 2016)
The performance of Malaysian students in Trends In Mathematics and Science Study (TIMSS) was not up to par. The rank of Malaysian students in the assessment is the bottom one third, not the top. However, there are still a very low number of studies have been conducted with the TIMSS finding. This study intends to a) confirm items reliability included in the study( for Malaysian students), b) confirm the significance of latent exogenous constructs toward latent endogenous construct and c) confirm the type of mediation exist in the structural model. Secondary data obtained from TIMSS 2011 database has been used in this study. Items have been grouped into latent exogenous constructs; school, teacher, motivation, self-confidence; latent mediator construct; attitude and latent endogenous construct; achievement. From the analysis, it is found that only a few items included are reliable to represent respective constructs. Furthermore, it is explored that all latent exogenous constructs have significant direct effects toward latent endogenous construct. And lastly, it has also been confirmed that, all latent exogenous constructs except school latent construct have indirect effects toward endogenous latent construct; students’ achievement through the mediator latent construct; attitude.